Takotsubo Cardiomyopathy in Two Patients without Any Cardiac Symptom on Maintenance Hemodialysis. (12th September 2013) - Muratsu, Jun; Morishima, Atsuyuki; Ueda, Hiroyasu; Hiraoka, Hisatoyo; Sakaguchi, Katsuhiko
Abstract : Takotsubo cardiomyopathy is a disorder characterized by left ventricular apical ballooning and electrocardiographic changes in the absence of coronary artery disease. While reversible in many cases, the mechanism of this disorder remains unclear. The most frequent clinical symptoms of takotsubo cardiomyopathy on admission are chest pain and dyspnea, resembling acute myocardial infarction. Here, we describe two cases of takotsubo cardiomyopathy without chest pain or dyspnea in patients on maintenance hemodialysis. The asymptomatic nature of these two cases may be due to the patients being on hemodialysis. Periodic electrocardiograms (ECG) may be helpful in screening this population for asymptomatic takotsubo cardiomyopathy and in evaluating its incidence.